The Holy One of Israel - Goodman, Lenn Evan (Oxford University Press, 2019)
Holiness in its constellation -- The presence of the holy -- Who is like God? -- To make a rainbow -- God and evil -- What is positive in negative theology? -- Natural law -- Revelation.